Pengembangan Bahan Ajar Menulis Puisi Bebas Kelas 8 SMP Xaverius Tugumulyo - Eti Irwanti (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2017)
This study aims to 1 find out the process of designing the development of teaching materials on writing free poetry of class 13 students of SMP Xaverius Tugumulyo, 2 to describe the teaching material of free class 13 class 13Tugumulyo SMP poetry, valid and effective. The method used Research and Development research and used model Dick and Carey. Interview data were analyzed using qualitative data analysis technique. The questionnaire value is used to determine the quantitative data. The design feasibility conclusion is included in the good kategoti, with the percentage of 80 percent. Results from validation of content or material feasibility are included in either category, with percentage of 80 percent. Last validation of language with good category, with percentage 74,28 percent. The validation results of the overall team of experts are categorized well, with the percentage of 78.33 percent. Practicality of teaching materials can be seen seen from the calculation of the validity of the instrument with the results of 0.98, with the category of validity is very high. The effectiveness of instructional materials and significant relationships can be seen from the calculations using SPSS 20, with a result of 0.0001. The conclusion of the research and development of teaching materials writing free poems that researchers have developed has been an alternative use in the process of teaching and learning. Keywords: Development, teaching materials, writing poetry.